Determinants of the Income of Farms in EU Countries - Średzińska , Joanna (Studia Oeconomica Posnaniensia, 2018)
The aim of the research was to identify determinants of the income of farms in the EU-15 as well as in Central and Eastern European countries and to assess how these determinants varied over time. The research was based on data from the FADN and it spanned the period from 2005 to 2013. Multiple regression was used to investigate the influence of selected variables on the income of farms. The analysis showed that apart from a wide range of similarities between farms in the EU-15 as well as in Central and Eastern European countries, there are also some differences between the determinants of their income. They usually refer to variables representing the production potential.